Effect of electric-magnetic compound field on the pore distribution in laser cladding process. (December 2018) - Zhang, Nan; Liu, Weiwei; Deng, Dewei; Tang, Zijue; Liu, Xuyang; Yan, Zhaorui; Zhang, Hongchao
Graphical abstract: Highlights: The electric-magnetic compound field was applied in laser cladding process. A new powder contained 92% AISI 316L and 8% TiH2 was adopted in the experiments. The pore distribution changed obviously under the influence of directional Ampere force. The cladding height showed a decreasing tendency with the increase of the downward Ampere force. The pore distribution changing mechanism was analyzed. Abstract: The porosity defect and the inhomogeneous pore distribution are intractable problems in the conventional laser cladding process and the laser melting porous metal separately. Therefore, it is necessary to develop a common approach to achieve the rational distribution of pores for different manufacturing processes. In this paper, electric-magnetic compound field has been applied to change the stress state of pores in the molten pool which obviously influenced the overflow speed of pores. In experiments, the laser cladding powder containing 92% AISI 316L and 8% TiH2 was adopted to obtain stable pore distribution. Results of experiments indicated that both the porosity and the pore size decreased and the pore distribution converged on the surface of the cladding layer when downward Ampere force was applied. Also an increasing tendency of porosity was observed and the pore distribution was more uniform when upward Ampere force was applied. The porosity decreased by 64.71% when the substrate current was 120 A while it increased by 144% when the substrate current was −90 A. The change of cladding shapes, microstructure and Vickers hardness of cladding layers under different Ampere force was also expounded.